Crystal structure of aminopentamide hydrogen sulfate, (C19H25N2O)(HSO4). Issue 4 (December 2022) - Kaduk, James A.; Gindhart, Amy M.; Gates-Rector, Stacy; Blanton, Thomas N.
Abstract : The crystal structure of aminopentamide hydrogen sulfate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Aminopentamide hydrogen sulfate crystallizes in space group P 21 / c (#14) with a = 17.62255(14), b = 6.35534(4), c = 17.82499(10) Å, β = 96.4005(6)°, V = 1983.906(14) Å 3, and Z = 4. The structure consists of layers parallel to the bc -plane with hydrogen sulfate anions at the core and aminopentamide cations on the outside. There is a strong charge-assisted O49–H53⋯O52 hydrogen bond between the hydrogen sulfate anions. This hydrogen bond links the anions in a chain parallel to the b -axis. The cation forms a discrete N–H⋯O hydrogen bond to the anion. The amide group also forms two weaker discrete hydrogen bonds to the anion. The three N–H⋯O hydrogen bonds link the cations and anions into columns parallel to the b -axis. This commercial material from USP contained an unidentified impurity, the powder pattern of which could be indexed on a monoclinic unit cell. The powder pattern has been submitted to ICDD for inclusion in the Powder Diffraction File™ (PDF®).